PENGEMBANGAN E-LKPD BERBASIS GUIDED DISCOVERY LEARNING PADA MATERI LAJU REAKSI - Nadera Beka Adenolira; Amir, Hermansyah; Elvinawati (University of Bengkulu, 2023)
Abstract This study aims to develop an e-LKPD based on Guided Discovery Learning and to determine the feasibility and student response to the e-LKPD. The development model used is the ADDIE model (analysis, design, development, implementation, evaluation) which is limited only to the development stage in the form of student response testing. The research was conducted from June to March 2023 at Bengkulu 1 Public High School. The research sample was taken by purposive sampling technique, namely class XI IPA 4, totaling 28 people for small group trials. The research instruments were interview sheets, student needs questionnaires, validation sheets, and student response questionnaire sheets. The resulting data consists of qualitative data in the form of suggestions from the validator and students as well as quantitative data on the results of validation sheets and student response questionnaires. Validation sheets and student response questionnaires use a Likert scale. The results showed that the chemical e-LKPD based on Guided Discovery Learning was declared very feasible by media and material experts with a media aspect percentage of 93.57% and a material aspect of 89.12%. Student responses to the e-LKPD were in the very good category with an average percentage of 91.13%, from the results of the study it could be concluded that the chemistry e-LKPD on Guided Discovery Learning-based reaction rates was very suitable for use as teaching materials. Keywords: e-LKPD; development; Guided Discovery Learning